The Effectiveness of 3D Animation Movie Media in Learning Literature in Junior High School - Nalan Meilia Sisi; Muhammad Fuad; Edi Suyanto; Munaris; Siti Samhati (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The purpose of this research is to develop a 3D animation movie and find out its feasibility and effectiveness in teaching literature in junior high schools. This research is a development-research. The development model adapts Borg and Gall's research and development procedures to the stages of (1) potential and problems; (2) collection of data needs; (3) development through product design and developing initial product forms; (4) product evaluation through validation by relevant experts/experts; (5) revision of the validation product design; (6) peer-to-peer product trials and limited-scale class trials and revisions to the trial results followed by large-scale class trials. Data collection techniques by observation, interviews, and questionnaires at Xaverius Way Halim Middle School Bandar Lampung. The results of the material expert test for the animated movie "Bunga Tidur" obtained a percentage of 96.1% in the very feasible category, media experts obtained a percentage of 97.0% in the very feasible category, and practitioners obtained a percentage of 95.0% in the very feasible category. The effectiveness of the animated movie Bunga Tidur was also tested and showed an average N-gain class VII-C of 0.68 including the medium category, an average N-gain class VII-D of 0.60 including the medium category, so this product was declared effectively used in learning.